Optimalisasi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti melalui Pendekatan Konstruktivistik di Sekolah Menengah Pertama - Nahadi, Muhammad Haris; Emawati, Emawati; Murzal, Murzal (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study explores implementing a constructivist approach in optimizing the learning process of Islamic religious education and character education at SMP Negeri 1 Narmada. The research method used is descriptive qualitative, with data analysis through data condensation, data presentation, and drawing and verifying conclusions. Extended observation techniques were used to ensure data validity. The study results indicate that implementing a constructivist approach can create a more interactive and participatory learning process. Methods such as small group discussions, mind mapping, and demonstrations can encourage active student involvement and cooperation. They not only passively receive material but also actively build understanding, connect knowledge with everyday experiences, and internalize moral and spiritual values. This study also found supporting factors, such as the role of teachers as facilitators, active student participation, and the availability of adequate facilities and learning resources. There are also inhibiting factors, such as peers and social media. Overall, the constructivist approach has been proven to increase deeper understanding, develop critical thinking skills, and shape positive attitudes in students in learning Islamic religious education and character education.